The processing of wax and wax additives with supercritical fluids - Schwarz, Cara Elsbeth (Stellenbosch : University of Stellenbosch, 2008)
Waxes have many potential uses but large-scale application is hampered by their virtual insolubility. By grafting the wax with a polyethylene glycol segment to form an alcohol ethoxylate, the solubility of the wax in commercial solvents is significantly increased. Alcohol ethoxylates are produced by the polymerisation addition of ethylene oxide onto an oxidised wax. Current methods of alcohol ethoxylate production from alcohols lead to wide ethylene oxide addition distribution and large quantities of residual alcohol. The objective of this study is to provide a method for narrowing the ethylene oxide distribution and to reduce the residual alcohol content. It is proposed to concentrate the alcohol ethoxylate in a post-production separation process using supercritical fluid extraction. The system is modelled to contain three pseudo-components: an alkane, an alcohol and an alcohol ethoxylate. Propane is selected as the supercritical solvent of choice due to the large solubility difference between the alkane and polyethylene glycol. Lower molecular weight alkane phase equilibrium data with propane is abundant but extrapolation to higher molecular weights requires further investigation as it may be complicated by molecular folding. Molecular folding occurs in crystalline polyethylene and high molecular weight normal alkanes but information regarding molecular folding in solution is inconclusive. A model is proposed for molecular folding of normal alkanes in supercritical solution. A high molecular weight alkane mixture is synthesised and phase equilibrium measurement with propane are conducted. A lower molecular weight alkane mixture is used to prove the application of the principle of congruency to high-pressure phase equilibria. In the high wax mass fraction region the measurements are between the no-folding and once-folded relationship, indicating the possibility of partial molecular folding. In the mixture critical and low wax mass fraction region the measurements are similar to the non-folding relationship. Molecular folding in solution is thus dependent on the solution concentration. No phase equilibria measurements exist for propane with either high molecular weight alcohols or alcohol ethoxylates. Measurements of propane with an alcohol mixture show total solubility below 140barA for temperatures up to 408K. Measurements of propane with an alcohol ethoxylate at temperatures between 378 and 408K shows that for an alcohol ethoxylate mass fraction between 0.025 and 0.5 pressures greater than 275barA are required for solubilisation. When comparing the solubility of the three pseudo-components, the alkane is the most soluble followed by the alcohol. The alcohol ethoxylate is the least soluble. A counter-current supercritical extraction process is proposed for the concentration of the alcohol ethoxylate. Pilot plant tests were conducted and the proposed set-up shows good separation. An estimate of the energy requirements shows that heating and cooling constitute the majority of the energy required but with the use of heat integration it can be reduced by approximately 33%. This work thus shows that the proposed process is both technically and economically viable. Although this work has provided a method for concentrating the alcohol ethoxylate, the process has not been optimised yet and future work includes the fine-tuning of this process.